Investment Climate Reforms : An Independent Evaluation of World Bank Group Support to Reforms of Business Regulations - Independent Evaluation Group (Washington, DC: World Bank, 2015)
The health of the private sector in developing countries depends on a well-functioning investment climate. The World Bank Group has provided extensive support to investment climate reforms. The Independent Evaluation Group assesses this support and makes several recommendations to enhance its overall effectiveness.